2019
DOI: 10.5650/jos.ess18217
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oil Type and Emulsifier on Oil Absorption of Steam-and-fried Instant Noodles

Abstract: The effects of four different frying oils and three emulsifiers on oil absorption by steam-and-fried instant noodles were evaluated. The blended oil (high oleic sunflower oil/soybean oil/palm oil = 24:25:1 (v/v/ v)) containing approximately 50% oleic acid was chosen as the proper frying oil due to lower oil absorption by instant noodle compared to palm, soybean, and high oleic sunflower oils. Among the four oils, the interfacial tension between high oleic sunflower oil and instant noodle was the lowest (0.073 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…In the production of fried instant noodles, mixtures of palm oil with partially hydrogenated soybean oil or rapeseed oil can also be used (Li et al, 2016). Qi et al (2019) studied the effects of four different types of oils (sunflower oil, palm oil, soybean oil, and blended oil) on the fat uptake of fried instant noodles. The finding demonstrated that fried instant noodles cooked in sunflower oil had the highest fat uptake (15.47%), followed by soybean oil (14.58%) and palm oil (14.30%).…”
Section: Oil Typementioning
confidence: 99%
See 3 more Smart Citations
“…In the production of fried instant noodles, mixtures of palm oil with partially hydrogenated soybean oil or rapeseed oil can also be used (Li et al, 2016). Qi et al (2019) studied the effects of four different types of oils (sunflower oil, palm oil, soybean oil, and blended oil) on the fat uptake of fried instant noodles. The finding demonstrated that fried instant noodles cooked in sunflower oil had the highest fat uptake (15.47%), followed by soybean oil (14.58%) and palm oil (14.30%).…”
Section: Oil Typementioning
confidence: 99%
“…In addition, the highest USFA level (sunflower oil) resulted in the greatest fat uptake by fried instant noodles, while the largest SFA level (palm oil) did not result in the greatest fat uptake, implying that the fatty acid composition of frying oil was not the key factor influencing fat uptake. On the other hand, some studies have shown that the fatty acid composition of oils has a strong relationship with their viscosity, impacting the oil absorption of final products (Kim et al, 2010;Qi et al, 2019;Yang et al, 2020). Ziaiifar et al (2008) reported that the oil viscosity can affect the amount of oil absorbed by fried foods.…”
Section: Oil Typementioning
confidence: 99%
See 2 more Smart Citations
“…In this regard, the influence and interaction of various ingredients and formulations as well as processing techniques on instant noodles' texture have also been investigated. Using CLSM and SEM, Qi et al (2019) analyzed surface properties and oil distribution in instant noodles and demonstrated the subsequent effects of four different frying oils and three emulsifiers on its oil absorption. Rise in quinoa proportion along with 40% feed moisture adjustment revealed more smooth surfaces as depicted through microstructure assessment (SEM) of extruded instant noodles (Tiga et al, 2021).…”
Section: Introductionmentioning
confidence: 99%